Studies on yield and economics of sunflower (Helianthus annuus L.) hybrids andvarieties as influenced by different fertilizer levels: EFFECT OF FERTILIZER LEVELS ON SUNFLOWER - V P SURYAVANSHI; S B SURYAWANSHI; M K GHODKE (Journal of Oilseeds Research, 2013)
A field experiment was conducted during the rainy season of 2008, 2009 and 2010 on Vertisol at Oilseeds Research Station, Latur to assess the productivity and response of sunflower (Helianthus annuus L.) hybrid and varieties to fertilizer inputs. Three hybrids along with two varieties were evaluated with four levels of fertilizer inputs. The result indicated that hybrids were superior over varieties. Sunflower hybrid LSFH-35, gave highestseed yield and monetary returns. The response to fertilizer was significant up to 150% RDF (90:45:45 NPK kg/ha).